Characteristics of conventional high-risk coronary plaques and a novel CT defined thin-cap fibroatheroma in patients undergoing CCTA with stable chest pain - Ahmed Salem; Joel Davis; Deepa Gopalan; James H.F. Rudd; Sarah C. Clarke; Peter M. Schofield; Martin R. Bennett; Adam J. Brown; Daniel Obaid (Clinical Imaging, 2023)
Background: Coronary computed tomography angiography (CCTA) can identify high-risk coronary plaque types. However, the inter-observer variability for high-risk plaque features, including low attenuation plaque (LAP), positive remodelling (PR), and the Napkin-Ring sign (NRS), may reduce their utility, especially amongst less experienced readers. Methodology: In a prospective study, we compared the prevalence, location and inter-observer variability of both conventional CT-defined high-risk plaques with a novel index based on quantifying the ratio of necrotic core to fibrous plaque using individualised X-ray attenuation cut-offs (the CT-defined thin-cap fibroatheroma - CT-TCFA) in 100 patients followed-up for 7 years. Results: In total, 346 plaques were identified in all patients. Seventy-two (21%) of all plaques were classified by conventional CT parameters as high-risk (either NRS or PR and LAP combined), and 43 (12%) of plaques were considered high-risk using the novel CT-TCFA definition of (Necrotic Core/fibrous plaque ratio of >0.9). The majority (80%) of the high-risk plaques (LAP&PR, NRS and CT-TCFA) were located in the proximal and mid-LAD and RCA. The kappa co-efficient of inter-observer variability (k) for NRS was 0.4 and for PR and LAP combined 0.4. While the kappa co-efficient of inter-observer variability (k) for the new CT-TCFA definition was 0.7. During follow-up, patients with either conventional high-risk plaques or CT-TCFAs were significantly more likely to have MACE (Major adverse cardiovascular events) compared to patients without coronary plaques (p value 0.03 & 0.03, respectively). Conclusion: The novel CT-TCFA is associated with MACE and has improved inter-observer variability compared with current CT-defined high-risk plaques.